Auditoría de gestión y su incidencia en el proceso de recuperación de cartera de crédito de la cooperativa de ahorro y crédito las naves ltda, provincia de Bolívar, periodo 2019-2020 - Moran Marmolejo, Santiago Bladimir (2021)
The objective of the research project is to evaluate the management of the financial advisors in the credit portfolio recovery processes of Cooperativa de Ahorro y Crédito Las Naves Ltda., verifying the processes executed in each of the stages, as well as identifying errors and non-compliances in the established procedures with the purpose of recommending solutions and strategies for portfolio recovery management. During the application of the audit, the documentation of the credit files available in the Cooperative was observed, compiled and examined. The results obtained show weaknesses in the portfolio recovery processes applied by the credit counselors, as well as the lack of training in member service, project evaluation and scarce presentation of monthly reports on portfolio recovery follow-up. The audit examination of credit management also determined the urgency of training loan officers and the creation of a staff of lawyers to expedite the recovery of portfolios that are in judicial and extrajudicial demand.